The Compound Profile of Chrysanthemum cinerariifolium (Trev.) Extract and Its Potential in Inhibiting COX-2 and CDK-4/6 Receptors in Oral Squamous Cell Carcinoma (OSCC) (In Silico Study) - anik - listiyana (Faculty of Medicine and Health Sciences, UIN Maulana Malik Ibrahim Malang, 2025)
Cancer is a disease that appears characterized by abnormal cell growth which can then infect adjoining parts of the body and or spread to other organs. One type of cancer that often occurs is Oral Squamous Cell Carcinoma (OSCC). There are several target receptors involved in cell proliferation, which are COX-2 and CDK-4/6 receptors. One of the herbal treatments for OSCC can be done using Chrsanthemum cinerariifolium (Trev.) herb extract. This research aims to find active compounds in Chrysanthemum cinerariifolium (Trev.) using UPLC-QToF-MS/MS method, the analysis of physiochemical prediction, toxicity analysis and molecular docking results on the proteins of COX-2 and CDK-4/6. This research combines two types of research, which are descriptive experimental for metabolite analysis and preexperimental one shot case study type for in silico test. The analysis of Metabolite compounds is using UPLC-QToFMS/MS Instrumentation, and for in silico tests using some SwissADME for physiochemical tests, PkCSM and Protox Online Tools for toxicity tests and Biovia Discovery Studio Visualizer and PyRx 0.8 for molecular docking tests. The results of this study obtained 28 compounds from metabolite profiling. And the results of molecular docking showed 1 compound with the best affinity on the tethering of both receptors. The compound is Diosmetin. There are also amino acid with 15 residues obtained in this process. However, the bonding value of native ligand with target protein is higher than the bonding of test ligand with target protein